The Impact of Environmental Variability on Ecological Systems - Vasseur, D.A; McCann, K.S (The Peter Yodzis Fundamental Ecology Series, 2007)
Fluctuations in the environmental conditions impacting life are ubiquitous. These fluctuations induce changes in the vital processes occurring within individual organisms (such as cellular metabolism) and the ecological processes occurring among individuals (such as competition, mutualism, and predation), ultimately leading to observable fluctuations in the commonly measured characteristics of ecological systems. From a very simple perspective, these processes are all modulators of environmental variability. We might best be able to understand the final form of this modulation - the impact of environmental variability on ecological systems - by building from an understanding of the responses of these life processes in isolation to an understanding of their responses in harmony. The impact of environmental variability on ecological systems is an issue that has been at the forefront of ecological research for many years. Research is taking place on many fronts, including theoretical mathematical based analyses, natural ecosystem observation and experimentation. This book brings together contributions from these three fronts to provide readers with a comprehensive look at the challenges for ecological systems and ecological research alike.